2015
DOI: 10.1186/s12964-015-0094-x
|View full text |Cite
|
Sign up to set email alerts
|

Small heat shock protein 20 (Hsp20) facilitates nuclear import of protein kinase D 1 (PKD1) during cardiac hypertrophy

Abstract: Background: Nuclear import of protein kinase D1 (PKD1) is an important event in the transcriptional regulation of cardiac gene reprogramming leading to the hypertrophic growth response, however, little is known about the molecular events that govern this event. We have identified a novel complex between PKD1 and a heat shock protein (Hsp), Hsp20, which has been implicated as cardioprotective. This study aims to characterize the role of the complex in PKD1-mediated myocardial regulatory mechanisms that depend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 28 publications
1
26
0
3
Order By: Relevance
“…Disruption of the small heat shock protein 20 (hsp20)-PKD interaction, which chaperones nuclear translocation of PKD1, inhibited nuclear import of PKD and β-AR induced hypertrophy (Sin et al, 2015). In microvascular endothelial cells, PKD1/HDAC7 signaling to FoxO1 initiates proangiogenic and proarteriogenic transcription by repression of CD36 transcription (Ren et al, 2016).…”
Section: Neurohormonal Stress-dependent Pkd Signalingmentioning
confidence: 99%
“…Disruption of the small heat shock protein 20 (hsp20)-PKD interaction, which chaperones nuclear translocation of PKD1, inhibited nuclear import of PKD and β-AR induced hypertrophy (Sin et al, 2015). In microvascular endothelial cells, PKD1/HDAC7 signaling to FoxO1 initiates proangiogenic and proarteriogenic transcription by repression of CD36 transcription (Ren et al, 2016).…”
Section: Neurohormonal Stress-dependent Pkd Signalingmentioning
confidence: 99%
“…Flag-tagged wild type and mutated human JAK1 were immunoprecipitated from transfected U4C cells solubilized in immunoprecipitation buffer using Flag M2-Sepharose beads prior to analysis by SDS-PAGE and immunoblotting as previously described (73).…”
Section: Pull-down Assays and Immunoprecipitationsmentioning
confidence: 99%
“…More recently, PKD1 was identified as a novel partner for HSPB6 and was suggested to bind directly to the HSPB6 to enable HSPB6 phosphorylation at a PKD1 consensus site, which contains serine 16 [77,78]. In the study of Sin et al, cardioprotection was reported to be induced by disruption of PKD1-HSPB6 complex, which should result in a reduction of HSPB6 phosphorylation [78]. The result contradicted the previous notion that increased PKA phosphorylation of HSPB6 functions as a cardioprotective mechanism [79].…”
Section: Anti-hypertrophic Actionmentioning
confidence: 93%
“…Disruption of the PDE4-HSPB6 complex which led to highly phosphorylated endogenous HSPB6 attenuated β-agonist-induced hypertrophy, highlighting the importance of phosphorylation status of HSPB6 on its cardioprotective effects [54]. More recently, PKD1 was identified as a novel partner for HSPB6 and was suggested to bind directly to the HSPB6 to enable HSPB6 phosphorylation at a PKD1 consensus site, which contains serine 16 [77,78]. In the study of Sin et al, cardioprotection was reported to be induced by disruption of PKD1-HSPB6 complex, which should result in a reduction of HSPB6 phosphorylation [78].…”
Section: Anti-hypertrophic Actionmentioning
confidence: 99%